2014
DOI: 10.1002/hyp.10236
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐comparison of high‐resolution gridded climate data sets and their implication on hydrological model simulation over the Athabasca Watershed, Canada

Abstract: Abstract:Several different gridded climate data sets have recently been made available with the purpose of providing a consistent set of climatic data for many hydro-climatic studies. Recent advances in land-surface schemes and their implementation in fully distributed processes-based hydrologic models have demanded even higher-resolution gridded data. It remains, however, a challenge to identify the most reliable gridded climate data for hydrologic modelling, especially in mountainous headwater regions where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 57 publications
5
55
0
Order By: Relevance
“…Dataset spread is also higher in the cold seasons, which is related to the challenges of accurate measurement of snowfall and the integration of unadjusted gauge data in some databases (e.g., UDEL and GPCC; Schneider et al, 2014). Eum et al (2014) also found the highest spread between precipitation analysis datasets during winter over higher elevation regions of the Athabasca watershed in northern Alberta. Other potential sources of difference are the inclusion of satellite retrievals, which are subject to sensor biases, in observational datasets (Serreze et al, 2005).…”
Section: Data and Methodsologymentioning
confidence: 86%
See 1 more Smart Citation
“…Dataset spread is also higher in the cold seasons, which is related to the challenges of accurate measurement of snowfall and the integration of unadjusted gauge data in some databases (e.g., UDEL and GPCC; Schneider et al, 2014). Eum et al (2014) also found the highest spread between precipitation analysis datasets during winter over higher elevation regions of the Athabasca watershed in northern Alberta. Other potential sources of difference are the inclusion of satellite retrievals, which are subject to sensor biases, in observational datasets (Serreze et al, 2005).…”
Section: Data and Methodsologymentioning
confidence: 86%
“…NARR 1979-present 32 km/ regional North America NCEP Mesinger et al (2006) Assimilates precipitation observations up to 2003 over Canada (Eum, Dibike, Prowse, & Bonsal, 2014). Several changes were induced in assimilation system in December 2002; PCP over Canada is not as good as hoped for because of small number of gauges available (Mesinger et al, 2006 Assimilates surface air temperature observations.…”
Section: Data and Methodsologymentioning
confidence: 98%
“…Most studies have focused on evaluating the performance of grid-based precipitation data in simulating hydrologic processes [15][16][17][18][19][20][21][22][23][24][25], while others have focused on evaluating the performances of different parameters in one data set in simulating hydrologic processes [26][27][28][29]. Some studies have evaluated the respective performances of different variables associated with multisource grid-based data in hydrologic modeling [30,31]. However, nearly 80% of water resources in the current region of interest are generated from snow and glacier melt.…”
Section: Introductionmentioning
confidence: 99%
“…CaPA-RDPA products are used in Canada for various environmental prediction applications, and in particular for hydrological modelling and forecasting (Eum et al, 2014; configuration of CaPA analysis is also embedded within the Canadian land-data assimilation system (CaLDAS), and thus contributes to the estimation of soil moisture, soil temperature and snow depth in real-time over Canada (Carrera et al, 2015). These state variables are then used to initialize Environment Canada's national High-Resolution Deterministic Prediction System (HRDPS) which provides 48-h experimental weather forecasts at 2.5 km horizontal resolution (Mailhot et al, 2010).…”
Section: Introductionmentioning
confidence: 99%